Composite Hydrogel of Poly(acrylamide) and Starch as Potential System for Controlled Release of Amoxicillin and Inhibition of Bacterial Growth - Ana V. Torres-Figueroa; Cinthia J. Pérez-Martínez; Teresa del Castillo-Castro; Enrique Bolado-Martínez; María A. G. Corella-Madueño; Alejandro M. García-Alegría; Tania E. Lara-Ceniceros; Lorena Armenta-Villegas (Journal of Chemistry)
Novel composite hydrogels of poly(acrylamide) (PAAm) and starch, at different ratios, were studied as potential platforms for controlled release of amoxicillin. The composite hydrogels were characterized by Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), and swelling kinetic measurements. The morphology analysis revealed the presence of starch granules well embedded within the PAAm network. The increase in starch content increased the rate of water uptake and the swelling degree at equilibrium. The amoxicillin release kinetics was sensitive to pH and temperature conditions. The in vitro bacterial growth inhibition of antibiotic-loaded hydrogels was tested though disc diffusion assays with Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 25923, and a carbapenemase producer Pseudomonas aeruginosa strain. The optimal release profile at physiological conditions and the powerful bacteria growth inhibition effects of amoxicillin-loaded hydrogels evidenced its potential for biomedical applications, particularly in oral administration and the local treatment of bacterial infections.